Sources of information for urban vegetable farmers in Accra, Ghana. (January 2017) - Osei, Simon K.; Folitse, Benjamin Y.; Dzandu, Lucy P.; Obeng-Koranteng, Grace
This study assesses sources of information for vegetable farmers in urban part of Accra, Ghana. One hundred vegetable farmers in the study area were sampled and interviewed using structured questionnaires. Findings revealed that urban vegetable farming is regarded as the business of men. Most of the urban vegetable farmers use radio as a source of agricultural information. Farmers use information on agrochemicals acquired in applying fertilizer, weedicides and pest control. A challenge to the urban vegetable farmers in Accra is poor public relations on the part of agricultural extension agents. The study recommends that the Ministry of Food and Agriculture roll out a programme to educate urban vegetable farmers on the various sources of agricultural information and sponsor adult education programmes in the local languages on national radio and television for farmers to help them make use of different sources of agricultural information effectively.